Confiabilidad test-retest y confiabilidad entre jueces de la prueba de clasificacion de objectos del Riley W. Cahndler en la muestra del I.D.P.E.M. - Morales Castilla, Luisa; Marcela, Brenda A.; Witzke, Don (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present study was aimed at providing reliability coefíicients over time, as well as between judges, for the Object Classification Test of Riley W. Gardner. The results show levels of reliability consistent with the fundamental changes associated with the developmental process. Inter-judge reliabilities for 50 protocols, scored independently by two judges, varied between .89 and 1.00.